Transcriptomic comparison of seeds and silique walls from two rapeseed genotypes with contrasting seed oil content - Guo, Xupeng; Yan, Na; Liu, Linpo; Yin, Xiangzhen; Chen, Yuhong; Zhang, Yanfeng; Wang, Jingqiao; Cao, Guozhi; Fan, Chengming; Hu, Zanmin (Frontiers in Plant Science, 2023)
Silique walls play pivotal roles in contributing photoassimilates and nutrients to fuel seed growth. However, the interaction between seeds and silique walls impacting oil biosynthesis is not clear during silique development. Changes in sugar, fatty acid and gene expression during Brassica napus silique development of L192 with high oil content and A260 with low oil content were investigated to identify key factors affecting difference of their seed oil content. During the silique development, silique walls contained more hexose and less sucrose than seeds, and glucose and fructose contents in seeds and silique walls of L192 were higher than that of A260 at 15 DAF, and sucrose content in the silique walls of L192 were lower than that of A260 at three time points. Genes related to fatty acid biosynthesis were activated over time, and differences on fatty acid content between the two genotypes occurred after 25 DAF. Genes related to photosynthesis expressed more highly in silique walls than in contemporaneous seeds, and were inhibited over time. Gene set enrichment analysis suggested photosynthesis were activated in L192 at 25 and 35 DAF in silique walls and at both 15 and 35 DAF in the seed. Expressions of sugar transporter genes in L192 was higher than that in A260, especially at 35 DAF. Expressions of genes related to fatty acid biosynthesis, such as BCCP2s, bZIP67 and LEC1s were higher in L192 than in A260, especially at 35 DAF. Meanwhile, genes related to oil body proteins were expressed at much lower levels in L192 than in A260. According to the WGCNA results, hub modules, such as ME.turquoise relative to photosynthesis, ME.green relative to embryo development and ME.yellow relative to lipid biosynthesis, were identified and synergistically regulated seed development and oil accumulation. Our results are helpful for understanding the mechanism of oil accumulation of seeds in oilseed rape for seed oil content improvement.